Pemindahan hak milik dalam instrumen Al-Ijarah Thumma Al-Bay’ (AITAB) di Malaysia - Muhammad Zin, Hakimah; Salamon, Hussin; Abdullah, Nurdianawati Irwani (Penerbit UTM Press., 2016)
The transfer of ownership at the end of a leasing contract is an important element in al-ijarah thumma al-bay’ (AITAB) structure. In AITAB structure, the ownership is transferred from owner to the hirer by the execution of a sale contract upon the expiry of the lease contract. The execution of sale contract must satisfy Shariah requirements. Nonetheless, legal framework of Islamic financial system in Malaysia which is subjected to civil law; and the absence of a comprehensive regulatory framework to govern AITAB transaction has caused the practice of AITAB in Malaysia to be subjected to the Hire Purchase Act 1967. Therefore, this study aims to identify the Shariah and legal issues that would arise in the implementation of ownership transfer in AITAB instrument as practised in Malaysia. This study also intends to determine the extent to which the Act is compatible to govern and enforce Syariah requirements in the execution of ownership transfer in AITAB transaction. This study employs qualitative methodology through document analysis. In its analysis, this study applies three methods; inductive, deductive and comparative methods. It analyses Syariah requirements in relations to ownership transfer and compares with the Hire Purchase Act 1967. The study also analyses the practice of ownership transfer in AITAB transaction in Malaysia. The finding of the study shows that the Hire Purchase Act 1967 possesses loopholes to govern and enforce Syariah requirements on ownership transfer in AITAB. Thus, the execution of ownership transfer in AITAB though satisfy Shariah requirements, would encounter legal issues.